AB0543 FEATURES ASSOCIATED WITH RENAL DAMAGE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS DECEASED OVER A 10-YEAR PERIOD. (June 2019) - Padjen, Ivan; Erceg, Marijan; Cerovec, Mislav; Mayer, Miroslav; Stevanovic, Ranko; Anic, Branimir
Abstract : Background: Renal damage (RD) is one of the most important contributors to morbidity and mortality in patients with systemic lupus erythematosus (SLE). Objectives: We aimed to assess features associated with RD in a group of 90 deceased SLE patients routinely followed-up at our institution, which serves as a national referral center for SLE. Methods: We retrospectively analyzed 90 SLE patients (68 females) deceased from 2002 to 2011. All patients were ≥18 years of age at death, fulfilling ≥4/11 classification criteria of the American College of Rheumatology (ACR). We identified patients with RD, as defined by the Systemic Lupus International Collaborating Clinics (SLICC)/ACR index. An extensive set of variables was compared between patients with and without RD (RD and RD-N, respectively): demographics, ACR criteria at diagnosis and cumulatively at death, total damage and its components one year following diagnosis and non-renal damage and its components cumulatively at death, as well as components of the metabolic syndrome, smoking, sicca and Hughes syndrome. Frequencies were compared using the chi-square and Fisher's exact test, and continuous variables using the t-test and Mann-Whitney U test. Variables associated with RD were analyzed using multivariate logistic regression. Results: We identified 25/90 patients who accrued RD over the course of their disease. In the univariate analysis, we found no difference between RD and RD-N patients in any of the following parameters: demographics, total count of ACR criteria at diagnosis and death, as well as damage at one year after diagnosis and cumulative non-renal damage at death. Compared to RD-N patients, RD patients had a higher proportion of malar rash at diagnosis (11/25 vs. 13/65, p=0.021) and a higher cumulative proportion of renal disorder (19/25 vs. 30/65, p=0.011), including proteinuria and urinary casts (17/25 vs. 23/65, p=0.005, for both). RD patients also had a higher proportion of myocardial infarction as an item of cumulative damage (7/25 vs. 6/65, p=0.023) and were more frequently obese (11/25 vs. 15/65, p=0.049). Conversely, hematological disorder and leukopenia at diagnosis were less frequent in RD compared to RD-N patients (4/25 vs. 30/65, p=0.008 and 1/25 vs. 21/65, respectively). In the final multivariate model (adjusted for gender, age at diagnosis and disease duration), malar rash at diagnosis and the cumulative presence of renal disorder (classification criteria of the ACR) were positively associated with RD. Conversely, leukopenia at diagnosis was inversely associated with RD (Figure 1 ). Conclusion: More than a quarter of deceased patients accrued RD. While malar rash at diagnosis may be associated with a higher likelihood of developing RD, early leukopenia may be associated with its lower likelihood in deceased patients. References: [1] Davidson A. Nat Rev Rheumatol. 2016;12:143-53. Disclosure of Interests: Ivan Padjen: None declared, Marijan Erceg: None declared, Mislav Cerovec: None declared, Miroslav Mayer Speakers bureau: Novartis, Sandoz, Abbvie, Pfizer, Alvogen, Roche, MSD, Octapharma, Ranko Stevanovic: None declared, Branimir Anic Speakers bureau: Novartis, Sandoz, Abbvie, Pfizer, Alvogen, Roche, MSD, Octapharma